2019
DOI: 10.1038/s41522-019-0107-4
|View full text |Cite
|
Sign up to set email alerts
|

Single microcolony diffusion analysis in Pseudomonas aeruginosa biofilms

Abstract: The influence of the biofilm matrix on molecular diffusion is commonly hypothesized to be responsible for emergent characteristics of biofilms such as nutrient trapping, signal accumulation and antibiotic tolerance. Hence quantifying the molecular diffusion coefficient is important to determine whether there is an influence of biofilm microenvironment on the mobility of molecules. Here, we use single plane illumination microscopy fluorescence correlation spectroscopy (SPIM-FCS) to obtain 3D diffusion coefficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 69 publications
(82 reference statements)
3
43
0
Order By: Relevance
“…3-BP is a low-molecular weight compound (166 g/mol), while molecular weight of bismuth subsalicylate (BIS) is more than two times higher (361 g/mol). A positive correlation between low-molecular weight of antimicrobials and their ability to penetrate the biofilm matrix has been already demonstrated by other research teams [ 47 , 48 ]. Therefore, it can be also assumed that low-weight 3BP would display significantly higher penetration through agar (a disk-diffusion assay) and biofilm matrix (an antimicrobial assay against lawn biofilms) compared to BIS.…”
Section: Discussionmentioning
confidence: 57%
“…3-BP is a low-molecular weight compound (166 g/mol), while molecular weight of bismuth subsalicylate (BIS) is more than two times higher (361 g/mol). A positive correlation between low-molecular weight of antimicrobials and their ability to penetrate the biofilm matrix has been already demonstrated by other research teams [ 47 , 48 ]. Therefore, it can be also assumed that low-weight 3BP would display significantly higher penetration through agar (a disk-diffusion assay) and biofilm matrix (an antimicrobial assay against lawn biofilms) compared to BIS.…”
Section: Discussionmentioning
confidence: 57%
“…The biofilm architecture of microcolonies, presence of EPS and water channels are often seen as contributors to the slowdown of convective transport and limit diffusion. It has been suggested that microcolonies act as molecular sieves and a diffusion coefficient is negatively correlated to the size of the colony 90 .…”
Section: Diffusion and Gradient Formation Of Reactive Species In Biofmentioning
confidence: 99%
“…Single plane illumination microscopy fluorescence correlation spectroscopy (SPIM-FCS). The protocol used was as previously described (80). Briefly, SPIM-FCS was used to quantitate the mobility of molecules diffusing in 3D in the biofilm matrix of the P. aeruginosa biofilm.…”
Section: Methodsmentioning
confidence: 99%